Photosynthetic conversion of CO2 to farnesyl diphosphate-derived phytochemicals (amorpha-4, 11-diene and squalene) by engineered cyanobacteria. Issue 1 (December 2016) - Choi, Sun; Lee, Hyun; Choi, Jaeyeon; Kim, Jiye; Sim, Sang; Um, Youngsoon; Kim, Yunje; Lee, Taek; Keasling, Jay; Woo, Han
Abstract Background Metabolic engineering of cyanobacteria has enabled photosynthetic conversion of CO2 to value-added chemicals as bio-solar cell factories. However, the production levels of isoprenoids in engineered cyanobacteria were quite low, compared to other microbial hosts. Therefore, modular optimization of multiple gene expressions for metabolic engineering of cyanobacteria is required for the production of farnesyl diphosphate-derived isoprenoids from CO2 . Results Here, we engineeredSynechococcus elongatus PCC 7942 with modular metabolic pathways consisting of the methylerythritol phosphate pathway enzymes and the amorphadiene synthase for production of amorpha-4, 11-diene, resulting in significantly increased levels (23-fold) of amorpha-4, 11-diene (19.8 mg/L) in the best strain relative to a parental strain. Replacing amorphadiene synthase with squalene synthase led to the synthesis of a high amount of squalene (4.98 mg/L/OD730 ). Overexpression of farnesyl diphosphate synthase is the most critical factor for the significant production, whereas overexpression of 1-deoxy-d -xylulose 5-phosphate reductase is detrimental to the cell growth and the production. Additionally, the cyanobacterial growth inhibition was alleviated by expressing a terpene synthase inS. elongatus PCC 7942 strain with the optimized MEP pathway only (SeHL33). Conclusions This is the first demonstration of photosynthetic production of amorpha-4, 11-diene from CO2 in cyanobacteria and production of squalene inS. elongatus PCC 7942. Our optimized modular OverMEP strain (SeHL33) with either co-expression of ADS or SQS demonstrated the highest production levels of amorpha-4, 11-diene and squalene, which could expand the list of farnesyl diphosphate-derived isoprenoids from CO2 as bio-solar cell factories.